PENERAPAN LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI DINAS PERHUBUNGAN KOTA SERANG - Dewi Asih; Pramudi Harsono (Universitas Bina Bangsa, 2021)
Performance is the appearance of work and the results achieved by a person either in goods or products or in the form of services which are usually used as a basis for self-assessment of the employee or the work organization concerned which reflects the employee's knowledge about his work. The higher the quality and quantity of the work, the higher the performance. This study aims to determine the effect of work environment and work discipline on a piecemeal basis on employee performance and the effect of work environment and work discipline together on employee performance at the Department of Transportation of Serang City. The type of research used is quantitative research. The research was conducted at the Department of Transportation of Serang City. The number of respondents is 35 people. This study distributed questionnaires to employees. The data processing and analysis technique used SPSS version 25. The results of this study indicate that the work environment (X1) has an effect on employee performance (Y) with a value of tcount > ttable (1,854>1,693). Work discipline (X2) has an effect on employee performance (Y) with a value of tcount > ttable (3,086>1,693) and simultaneously or simultaneously shows that Fcount > Ftable, namely = 28,400 > 3,29. This means that there is an influence between the Work Environment and Work Discipline together on the Performance of Employees at the Serang City Transportation Service. The conclusion obtained shows that the work environment partially affects employee performance, partially work discipline affects employee performance and simultaneously or simultaneously the work environment and work discipline affects employee performance